Structural brain abnormalities in patients with type I bipolar disorder and suicidal behavior. (30th July 2017) - Duarte, Dante G.G.; Neves, Maila de Castro L.; Albuquerque, Maicon R.; Turecki, Gustavo; Ding, Yang; de Souza-Duran, Fabio Luis; Busatto, Geraldo; Correa, Humberto
Abstract: Some studies have identified brain morphological changes in the frontolimbic network (FLN) in bipolar subjects who attempt suicide (SA). The present study investigated neuroanatomical abnormalities in the FLN to find a possible neural signature for suicidal behavior in patients with bipolar disorder type I (BD-I). We used voxel-based morphometry to compare euthymic patients with BD-I who had attempted suicide (n=20), who had not attempted suicide (n=19) and healthy controls (HCs) (n=20). We also assessed the highest medical lethality of their previous SA. Compared to the participants who had not attempted suicide, the patients with BD-I who had attempted suicide exhibited significantly increased gray matter volume (GMV) in the right rostral anterior cingulate cortex (ACC), which was more pronounced and extended further to the left ACC in the high-lethality subgroup (p<0.05, with family-wise error (FWE) correction for multiple comparisons using small-volume correction). GMV in the insula and orbitofrontal cortex was also related to suicide lethality (p<0.05, FWE-corrected). The current findings suggest that morphological changes in the FLN could be a signature of previous etiopathogenic processes affecting regions related to suicidality and its severity in BD-I patients. Highlights: Brain morphometric abnormalities in bipolar patients related to suicide attempt and medical lethality. Increased anterior cingulate cortex related to suicide attempt and severity; Abnormal volume in insula and orbitofrontal cortex related to suicide lethality; Frontolimbic network could be neuro-marker of suicidality in bipolar diagnoses.